Damage mapping and monitoring in sublevel caving crosscuts at the Malmberget mine - Jones, TH; Saiang, David (Caving 2022: Fifth International Conference on Block and Sublevel Caving, 2022)
The LKAB’s Malmberget mine in Sweden is one of the largest sublevel caving mines in the world, with an annual production rate averaging 18 million tons. This high rate of production at depth (>1,000 m) creates significant mining-induced stress redistribution on a global scale. At a production-level scale, this redistribution results in undesirable amounts of deformation in the entries and typically leads to general degradation in the footwall contact zones. This is exacerbated by highly varied geological and geotechnical characteristics of the lithology often found in the contact zone. To better understand the impact of mininginduced stress on production level entries, a study was conducted to measure stress changes and associated deformation over a two year period, as mining progressed in the vicinity of the instrumentation. Three-dimensional relative stress measurements using digital hollow inclusion stress cells and multiple-point borehole extensometer measurements were combined with convergence and floor heave measurements and regular damage mapping throughout the contact zone to better understand the evolution of damage in these areas. A site-specific Entry Condition Rating (ECR) system was developed to help geomechanics better track and understand the expected performance of the crosscut given the current state of mining. The result of the work is a better understanding of where and when damage is expected to occur, and the ability to properly time the installation of secondary support in a pre-emptive manner. Funder: Luossavaara Kiirunavaara AB (406); ISBN för värdpublikation: 978-0-6450938-3-4 Design Methods for Variable Stress, Variable-Geology Environments